Efficiency Analysis of Takaful Companies' Performance Using Stochastic Frontier Analysis Approach: A Comparison Between Southeast Asia and The Middle East Regions - Nur Kholis; Rakhmawati (Millah: Journal of Religious Studies, 2022)
This study aims to measure the efficiency of Takaful companies in Southeast Asia and the Middle East region. The efficiency level of Takaful companies in Southeast Asia and the Middle East region was examined from 2016 to 2020. The sample consisted of 23 companies in Indonesia, 14 in Malaysia, three in UEA, and 31 in Saudi Arabia. The efficiency value of Islamic insurance companies was calculated using the Stochastic Frontier Analysis (SFA) method, afterward, the Mann-Whitney test was performed. The results showed that the efficiency median value of the companies in Southeast Asia was lower compared to the Middle East with respective values of 0.26 and 0.32. It was concluded from the results of the Mann-Whitney test that the differences in the median efficiency value of Islamic insurance companies in Southeast Asia and the Middle East were not significant. The novelty of this research is to provide new and significant information on the performance of Takaful Companies during 2016-2020. The results of this study have significant implications for policymakers in each of the countries examined to understand the efficiency condition of Takaful companies in the region. Furthermore, policymakers in Southeast Asia need to promote low-efficiency Takaful operators to expand their business. The lowest efficiency score for Takaful companies is in Indonesia, especially for small Takaful companies. The implication is that the Indonesian government or related agencies need to increase the popularity of Takaful companies among the public so that income and efficiency increase.